(Avoidant Attachment and its Relationship with Psychological Abuse) (Journal of the College of Basic Education, 2022)
This study aims at investigating:1-The degree of Avoidant Attachment Among middle school Students. 2- Is the level Psychological Abuse Among middle school Students 3-The relationship between the Avoidant Attachment and the Psychological Abuse Among middle school Students . 4-Difference in relationship according to sex variable In order to achieve the research objectives, the researcher adopted the Hazan scale, which was translated by (Abbas 2017), consisting of (19) paragraphs and three alternatives to measure avoidance attachment, and adopted a measure (dakhel 2009), consisting of (23) paragraphs and three alternatives to measure psychological abuse, The results showed that the degree of avoidance attachment in intermediate students was (45 ) and the degree of psychological abuse was also (51 ), but the relation between the two variables is (+ ), and the results showed that there was no Statistical differences between variables according to gender variable